Predictive utility of the NEO-FFI for later substance experiences among 16-year-old adolescents - Parchetka, Caroline; Strache, Nicole; Raffaelli, Bianca; Gemmeke, Isabel; Weiß, Katharina; Artiges, Eric; Banaschewski, Tobias; Bokde, Arun; Bromberg, Uli; Buechel, Christian; Conrod, Patricia; Desrivières, Sylvane; et al. (Springer Verlag, 2016)
Purpose